2017
DOI: 10.1503/cmaj.160427
|View full text |Cite
|
Sign up to set email alerts
|

Team-based versus traditional primary care models and short-term outcomes after hospital discharge

Abstract: INTERPRETATION:Our study showed that enrolment in the newer team-based primary care practices was associated with lower rates of postdischarge emergency department visits and death. We did not observe differences in readmission rates, which suggests that more targeted or intensive efforts may be needed to affect this outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…Team-based care may improve outcomes and job satisfaction. [25][26][27] However, the results are consistent with literature suggesting that involvement of multiple healthcare professionals does not necessarily constitute team-based care: outcomes associated with teams may not be transferrable to 'groups' or 'pseudoteams', as reflected in some participants' descriptions. [28][29][30] It is also questionable whether other healthcare providers and patients would agree that the GP (or GP-patient dyad) is the 'conductor of the orchestra' (GP12).…”
Section: Discussionsupporting
confidence: 83%
“…Team-based care may improve outcomes and job satisfaction. [25][26][27] However, the results are consistent with literature suggesting that involvement of multiple healthcare professionals does not necessarily constitute team-based care: outcomes associated with teams may not be transferrable to 'groups' or 'pseudoteams', as reflected in some participants' descriptions. [28][29][30] It is also questionable whether other healthcare providers and patients would agree that the GP (or GP-patient dyad) is the 'conductor of the orchestra' (GP12).…”
Section: Discussionsupporting
confidence: 83%
“…Although the Utah, 10 Seattle 13 and Ontario 20 groups reported higher rates of some quality-of-care measures in team-based practices, it is important to note that not all process measures were improved in any of the settings -for example, blood pressure control rates were lower with team-based care in Utah and cancer screening rates were lower in Ontario. We were unable to examine quality of care in this study, although such an evaluation is currently ongoing in Alberta.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…1,2,[10][11][12][13] An early evaluation of the first wave of Alberta primary care networks reported that individuals with newly diagnosed diabetes had better glycemic control and lower rates of emergency department visits or hospital admissions for hyper-or hypoglycemia in 2007 if treated in 1 of the 18 primary care networks at that time. 1 However, the benefits were small: glycated hemoglobin (HbA 1C ) was 0.07 lower and the absolute reduction in emergency department visits or hospital admissions was 0.7 per 1000 patient-months.…”
mentioning
confidence: 99%
“…For example, implementing transitional care teams in acute care reduces costs and patient readmissions, and increases provider and patient satisfaction [5]. In primary care, evidence shows that team-based care improves patient and provider satisfaction, lowers rates of health care utilization (eg, emergency department visits, ambulatory care visits, and primary care physician encounters), and lowers post-discharge mortality [6][7][8].…”
Section: Emerging Payment Modelsmentioning
confidence: 99%